2016
DOI: 10.1016/j.jmau.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Histological study on the protective effect of endogenous stem-cell mobilization in Adriamycin-induced chronic nephropathy in rats

Abstract: Chronic kidney disease is a global health problem with increasing morbidity and mortality. Therefore, this study was planned to test the protective effect of hematopoietic-stem-cell mobilization by granulocyte colony-stimulating factor (G-CSF) on Adriamycin (ADR)-induced chronic renal disease in rats. Thirty albino rats were equally divided into three groups: control, ADR group [rats received a single intravenous injection of ADR (5 mg/kg)], and G-CSF group [rats received ADR by the same route and the same dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Histological finings revealed nearly normal renal architecture. This was confirmed by others [30] . who stated that G-CSF improved mobilization of endogenous hemopoietic stem cells (HSCs), so restored normal renal structure and reduced renal injury and development of reactive oxygen species (ROS) and levels of urea and creatinine.…”
Section: Mobilizationsupporting
confidence: 84%
“…Histological finings revealed nearly normal renal architecture. This was confirmed by others [30] . who stated that G-CSF improved mobilization of endogenous hemopoietic stem cells (HSCs), so restored normal renal structure and reduced renal injury and development of reactive oxygen species (ROS) and levels of urea and creatinine.…”
Section: Mobilizationsupporting
confidence: 84%
“…Regarding vascular alterations, consistent with our results, other studies have reported that different nanoparticles with different sizes resulted in expanded and congested renal tubular capillaries with inflammatory infiltration [ 29 , 32 ]. It has been reported that cell infiltration is a sign of atrophy of tubular cells in chronic kidney diseases [ 38 ]. This inflammatory response seems to be a result of the oxidative stress caused by AgNPs, contributing to vascular congestion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers contributed this finding and the observable interrupted basal laminae to ROM generation which led to rapid loss of cytoskeletal integrity. [37]…”
Section: Discussionmentioning
confidence: 99%